A microfluidic, dual-purpose sensor for in vitro detection of Enterobacteriaceae and biotinylated antibodies. Issue 7 (4th March 2016) - Kokkinis, G.; Plochberger, B.; Cardoso, S.; Keplinger, F.; Giouroudi, I.
Abstract : A bacteria and antibody biosensor where friction is for the first time used for resolving biomolecules. Abstract : In this paper, we present a versatile, dual-purpose sensor for in vitro detection of Enterobacteriaceae ( e.g. Escherichia coli ) and biotinylated antibodies ( e.g. IgG rabbit polyclonal antibodies), based on different detection principles for each bioanalyte. These bioanalytes are tagged individually with functionalized magnetic microparticles, suspended into a static fluid and injected into a microfluidic channel. Without the need for bulk or complicated pumping systems, the functionalized microparticles are set in motion by a magnetic force exerted on them by integrated microconductors. The fundamental detection principle is the decrease in the velocity of the microparticles that are loaded with the respective bioanalyte, due to factors inhibiting their motion. The velocity of the unloaded, bare microparticles is used as a reference. We discovered a novel mechanism on which the constrained particle motion is based; in the case of E. coli, the inhibiting factor is the enhanced Stokes' drag force due to the greater volume and altered hydrodynamic shape, whereas in the case of biotinylated antibodies, it is the increased friction force at the interface between the modified microparticle and the biosensor's surface. Friction force is for the first time employed in a scheme for resolving biomolecules. Integrated magnetic microsensors are used for the velocity measurements by detecting the microparticles' stray field. Moreover, we developed a biocompatible, easy to implement and reliable surface modification that practically diminishes the problem of bioadhesion on the sensor's surface.